Correlation analysis of serum FGLP1, UACR and the risk of heart failure in patients with type 2 diabetes: Serum FGLP1, UACR and the risk of heart failure in T2D - Xia, Lianheng; Guo, Yingshuo; Wang, Jiaxin; Wang, Tingxuan; Xu, Chunhui; Song, Meiyu; Du, Chang; Wang, Qingjie; Gao, Jie (Journal of Medical Biochemistry, 2026)
Objective To explore the correlations between serum FGLP1 (Fibrinogen-like protein 1 C-terminal peptide) levels, the urine albumin-to-creatinine ratio (UACR) and left ventricular diastolic dysfunction (LVDD) in elderly patients with type 2 diabetes mellitus (T2DM).Methods From August 2023 to August 2025, 256 elderly patients with T2DM who were admitted to our hospital were selected as the case group, and 120 healthy individuals who underwent physical examinations were selected as the control group. In accordance with the diagnostic criteria for LVDD, T2DM patients were divided into a disorder group (n=70) and a nondisorder group (n=186), and single-factor analysis, multivariate logistic regression analysis, and Spearman correlation analysis were performed to explore the correlation between serum FGLP1 levels, UACRs and LVDD in T2DM patients, and receiver operating characteristic curves were used to evaluate the ability of serum FGLP1 levels and urine UACR to predict LVDD.Results The serum FGLP1 concentration and urine UACR were higher in the case group than in the healthy group (P
Keywords: Type 2 diabetes; Left ventricular diastolic dysfunction; Fibrinogen-like protein 1 C-terminal peptide; Urinary albumin-to-creatinine ratio